Estimasi Emisi Gas Rumah Kaca (GRK) di TPA Benowo Menggunakan Model LandGem: Estimation of Green House Gas (GHG) Emissions at Benowo Landfill Using the LandGem Model - Rimadhani Prilindatami; Okik Hendriyanto Cahyonugroho (LPPM Universitas Mataram, 2023)
Greenhouse gases (GHG) are one of the dangerous gases that cause global warming. Greenhouse gases include methane gas and carbon dioxide. In large quantities, this gas can cause damage to the atmosphere. Greenhouse gas emissions are dominated by waste management activities at landfills. Benowo Landfill is one of the Landfills that manages the waste of the residents of Surabaya City. The more waste that is piled up in the landfill, the more gas is produced. So it is necessary to estimate the occurrence of methane gas and carbon dioxide gas in landfills. LandGem is a model that is able to estimate greenhouse gases that will appear in landfills. In this research, greenhouse gas estimates were carried out at the Benowo landfill using 3 scenarios. This scenario is applied to determine the influence of weather (k value) on the landfill. The results showed that scenario 3 which uses a k value of 0.7 (wet area) has the highest estimate of methane and carbon dioxide compared to the other scenarios, namely 6.801 x 107 m3/year. This happens because the k value means that the landfill area has high rainfall and there is a bioreactor or leachate circulation system. This value is considered a good value for bacterial growth in landfills.